Microstructural and Mechanical Studies of PVA Doped with ZnO and WO3 Composites Films. (21st January 2014) - Rithin Kumar, N. B.; Crasta, Vincent; Bhajantri, Rajashekar F.; Praveen, B. M.
Abstract : Polymer composites of ZnO and WO3 nanoparticles doped polyvinyl alcohol (PVA) matrix have been prepared using solvent casting method. The microstructural properties of prepared films were studied using FTIR, XRD, SEM, and EDAX techniques. In the doped PVA, many irregular shifts in the FTIR spectra have been observed and these shifts in bands can be understood on the basis of intra/intermolecular hydrogen bonding with the adjacent OH group of PVA. The chemical composition, phase homogeneity, and morphology of the polymer composites of the polymer film were studied using EDAX and SEM. These data indicate that the distribution of nanosized ZnO and WO3 dopants is uniform and confirm the presence of ZnO and WO3 in the film. The crystal structure and crystallinity of polymer composites were studied by XRD. It was found that the change in structural repositioning and crystallinity of the composites takes place due to the interaction of dopants and also due to complex formation. The mechanical studies of doped polymer films were carried out using universal testing machine (UTM) at room temperature, indicating that the addition of the ZnO and WO3 with weight percentage concentration equal to 14% increases the tensile strength and Young's modulus.